Democracy and Welfare according to liberal and democratic militancy: The Gaither Report and the Ford Foundation’s international policy agenda - Chaves, Wanderson da Silva (Oikos, 2009)
This article deal with some commonplaces concerning United States political agendas from post-Second World War. The Ford Foundation international agenda, made around the end of 40’s, will be employed as example and synthesis about this commonplace. Herewith, it will be possible to identify the fi rst American proposal emerging from the Cold War in its time of outbreak.